Advances and Perspectives for Genome Editing Tools of Corynebacterium glutamicum - Wang, Qingzhuo; Zhang, Jiao; Al Makishah, Naief H.; Sun, Xiaoman; Wen, Zhiqiang; Jiang, Yu; Yang, Sheng (Frontiers in Microbiology, 2021)
Corynebacterium glutamicum has been considered a promising synthetic biological platform for biomanufacturing and bioremediation However, there are still some challenges in genetic manipulation of C. glutamicum. Recently, more and more genetic parts or elements (replicons, promoters, reporter genes, and selectable markers) have been mined, characterized, and applied. In addition, continuous improvement of classic molecular genetic manipulation techniques, such as allelic-exchange via single/double-crossover, nuclease-mediated site-specific recombination, RecT-mediated single-chain recombination, actinophages integrase-mediated integration, and transposition mutation, have accelerated the molecular study of C. glutamicum. More importantly, emerging gene editing tools based on CRISPR/Cas system is revolutionarily rewriting the pattern of genetic manipulation technology development for C. glutamicum, which made gene reprogramming, such as insertion, deletion, replacement, point mutation, etc. much more efficient and simpler. This review summarized recent progress in molecular genetic manipulation technology development of C. glutamicum, and discussed the bottlenecks and perspectives for future research of C. glutamicum as a distinctive microbial chassis.